Different phenotypes of mitral regurgitation in patients with right apical ventricular pacing: An echocardiographic approach in a heterogeneity of clinical scenario - Chango Azanza, Diego Xavier (2021)
The right ventricular (RV) apical pacing causes a dyssynchronous activation of the left ventricle and the papillary muscles, which determines the decline of the left ventricular ejection fraction (LVEF) in addition to inadequate closure of the valvular apparatus with the presence of different degrees of mitral valve regurgitation. The study of this condition is relevant in clinical decision-making to define patients who benefit from cardiac resynchronization for the relief of symptomatic mitral regurgitation. However, there is a wide heterogeneity of conditions and pathologies that can coexist with different degrees of cardiomyopathies in these patients, which makes etiological determination challenging and worsens the clinical course. The transthoracic echocardiography allows us the comprehensive assessment of mitral valve regurgitation and ventricular function parameters as well as mechanical dyssynchrony as a result of the artificial pacing.